2023
DOI: 10.1177/0021955x231162799
|View full text |Cite
|
Sign up to set email alerts
|

Development and characterization of sandwich panels for thermal insulation in a cold storage chamber

Abstract: Sandwich composites are materials that have superior properties including low weight, high impact energy absorption and high thermal insulation features, compared to conventional materials. In this study, four different sandwich samples were explored for use in cold storage chambers. The composites were created using an injection molding process with polyurethane foam as the core and different materials (glass fiber reinforced polyester, galvanized steel, aluminum sheets and crimped aluminum) as face materials… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 39 publications
0
0
0
Order By: Relevance
“…Durmuş, G. & Topuz, H. C. (2022) used expanded perlite and granular polystyrene foam as aggregates in foam concrete, as well as creating an aerogel layer on the concrete surface. MAHS Khan et al (2018) studied the low-velocity impact of EPS-based composite, finding non-linear displacement and linear maximum principal strain increase with impact energy, causing damage after 8J.Four different sandwich samples were explored for use in cold storage chambers, and the results showed that polyurethane had a homogeneous distribution of size and shape with closed cells, which can improve the retention of the insulation gas (Sartori, Ana P. et al 2023). The perlite-based insulating material is developed to meet ASTM C610 standards in a form of the board in order to meet the requirements of thermal conductivity and moisture resistance (Keawprak, N. et al 2022).…”
Section: Introductionmentioning
confidence: 99%
“…Durmuş, G. & Topuz, H. C. (2022) used expanded perlite and granular polystyrene foam as aggregates in foam concrete, as well as creating an aerogel layer on the concrete surface. MAHS Khan et al (2018) studied the low-velocity impact of EPS-based composite, finding non-linear displacement and linear maximum principal strain increase with impact energy, causing damage after 8J.Four different sandwich samples were explored for use in cold storage chambers, and the results showed that polyurethane had a homogeneous distribution of size and shape with closed cells, which can improve the retention of the insulation gas (Sartori, Ana P. et al 2023). The perlite-based insulating material is developed to meet ASTM C610 standards in a form of the board in order to meet the requirements of thermal conductivity and moisture resistance (Keawprak, N. et al 2022).…”
Section: Introductionmentioning
confidence: 99%